METAPHOR AND EMOTIONAL FRAMING IN UZBEK MEDIA DISCOURSE ON SOCIAL JUSTICE - Ilhom Haydarov Tukhtayevich (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article investigates the linguistic strategies of metaphor and emotional language in Uzbekistan’s press discourse on social justice. Drawing on critical discourse analysis and conceptual metaphor theory, the study examines how abstract notions of justice, fairness, and inequality are concretized through figurative language. Examples from Uzbek media illustrate that metaphors such as “justice is a foundation” construct social reality by emphasizing stability and moral order. Emotional language, including negatively charged lexical items like “we distanced ourselves from justice,” serves to provoke public empathy and mobilize civic awareness. While these strategies enhance rhetorical impact, their ethical use remains crucial to avoid manipulation or oversimplification. The article highlights the intersection of state policy, national values, and global justice discourse in the Uzbek context.